Melacak Jejak Situs Arkeologi dari Sastra Lisan - Hari Suroto (Balai Bahasa Provinsi Papua, 2019)
Archeology is a part of science that can not stand alone, so id needs other knowledge. To find archeology remain or archeological site, the archeolog take the first information from the people and writing source. Papua tradition on past is oral tradition, so it difficult for archeolog to find archeology remain or archeological site. But Papua richer the folklore that can be history and place source. Folklore using as the first information on archeology research is the new thing, and it can apply on Papua.